Goh Keng Swee a legacy of public service - Chew, Emrys; Kwa, Chong Guan.; ebrary, Inc. (Singapore ; Hackensack, N.J. : World Scientific, 2012)
"Dr. Goh Keng Swee's extensive career as a public servant was dynamic as well as distinguished, in many ways decisively instrumental in the making of the Republic of Singapore. This distinctive collection of essays attempts an assessment of the long-term influence and significance of Dr. Goh's major contributions. Commissioned as a companion volume to Goh Keng Swee: A Public Career Remembered, this volume brings together an exceptional team of Singaporean scholars whose interdisciplinary expertise and cross-generational perspectives offer a balanced analysis and nuanced appraisal of Dr. Goh's lifetime of public service. The book's contributors argue that Dr. Goh's past endeavours bequeathed an enduring legacy, meriting fresh examination and careful evaluation in order to appreciate the heroic scale of such achievement. Particularly instructive are the examples of Dr. Goh's thinking patriotism, fiscal prudence, strategic pragmatism, and creative imagination at work -- technocracy at its finest -- which could be of immediate, practical benefit to a wider 'nation of technocrats'. Further illumination comes from the insights of those contributors who had worked with the former Deputy Prime Minister and knew him personally."--Publisher's description.
Introduction : Goh Keng Swee, heroic architect and master builder of modern Singapore / Emrys Chew -- Goh Keng Swee in a social welfare history of Singapore / Ho Chi Tim -- Goh Keng Swee in politics and parliament / Kevin Y.L. Tan -- Goh Keng Swee, the development economist / Lee Soo Ann -- Goh Keng Swee and finance / Linda Low -- Goh Keng Swee and the emergence of a modern SAF : the rearing of a poisonous shrimp / Bernard Fook Weng Loo -- Goh Keng Swee and Singapore's defence industrial policy / Adrian Wee Jin Kuah -- Goh Keng Swee and the Singapore education system / Alistair Chew -- Goh Keng Swee's contributions to higher education, military studies, and the research institutes / Ernest Chew -- Goh Keng Swee and Chinese studies in Singapore : from Confucianism to "China watching" / John Wong -- Goh Keng Swee's cultural contributions and the making of the Singapore Symphony Orchestra / Bernard T.G. Tan.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Goh, Keng Swee, -- 1918-2010.; Statesmen -- Singapore -- Biography; Cabinet officers -- Singapore -- Biography; Singapore -- Politics and government -- 20th century; Electronic books